Economic valuation of Lansa Mangrove Forest, North Sulawesi, Indonesia - CALVYN FA SONDAK; ERLY Y KALIGIS; ROBERT A BARA (Society for Indonesian Biodiversity, 2019)
Abstract. Sondak CFA, Kaligis EY, Bara RA. 2019. Economic valuation of Lansa Mangrove Forest, North Sulawesi, Indonesia. Biodiversitas 20: 978-986. Mangrove forest gives many benefits and services to human and environment. Even though it contributes many benefits and services, coastal ecosystems threatened as one of the most critical ecosystems in the world. The study aims to estimate the economic value of ecosystem services provided by Lansa mangrove forest, Wori Sub-district, North Minahasa District, North Sulawesi Province, Indonesia. Here, we describe the use value (direct and indirect value) and non-use value (option and existence value), and emphasize the components of ecosystem services fish resources, firewood, coastal protection, biodiversity, carbon (C) removal and mangrove sustainability because these directly influence human welfare. Their market price calculated fish and C removal value. Coastal barrier and firewood were approached using the replacement cost method. Biodiversity value was calculated using Indonesia mangrove forest biodiversity value. Contingent Valuation method was used to find out people willing to pay for the sustainability of mangrove forest. Lansa mangrove forest total economic value (TEV) was IDR 4,431,197,603 or equal to US 305,600 (US 1,959 ha-1). The success of this mangrove valuation has potentially large implications for future policy-making of its’ ecosystem service values.